2017
DOI: 10.1155/2017/5179271
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Brain Metabolomic Variations Reveal Perturbation of Sleep Deprivation on Rats and Ameliorate Effect of Total Ginsenoside Treatment

Abstract: Sleep loss or sleep deprivation (SD) refers to shorter sleep than average baseline need, and SD has been a serious problem of modern societies which affects health and well-being. Panax ginseng is a well-known traditional Chinese medicine (TCM). Our previous study has demonstrated that total ginsenosides (GS), the extracts from Panax ginseng, could effectively improve cognition and behavior on SD rats. However, little is known about its metabolomic study. In this study, serum and brain metabolomic method based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 69 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…The three BCAAs are key elements in the de novo synthesis of glutamate [ 93 ]. An excess of BCAAs caused by sleep-wake disorders, can reduce the uptake of the serotonin precursor tryptophan and the catecholamine precursors tyrosine and phenylalanine; therefore, the decreased inhibitory neurotransmitters (serotonin and catecholamines) and increased excitatory neurotransmitters (glutamate and aspartate) might maintain the waking of the brain [ 68 ]. Elevation of BCAAs during nighttime has also been linked to daytime fatigue, likely due to their capacity to reduce the transport of tryptophan through the blood–brain barrier, finally affecting serotonin levels [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The three BCAAs are key elements in the de novo synthesis of glutamate [ 93 ]. An excess of BCAAs caused by sleep-wake disorders, can reduce the uptake of the serotonin precursor tryptophan and the catecholamine precursors tyrosine and phenylalanine; therefore, the decreased inhibitory neurotransmitters (serotonin and catecholamines) and increased excitatory neurotransmitters (glutamate and aspartate) might maintain the waking of the brain [ 68 ]. Elevation of BCAAs during nighttime has also been linked to daytime fatigue, likely due to their capacity to reduce the transport of tryptophan through the blood–brain barrier, finally affecting serotonin levels [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of hypoxanthine can be considered a sign of less degradation of adenosine, indicating higher concentrations of adenosine in biofluids in the body [33]. In sleep loss or sleep deprivation experimental model groups, serum adenosine was elevated, but its product of degradation, hypoxanthine, was decreased, suggesting disordered nucleotide metabolism [34]. It was reported that with increasing grazing intensity, sheep decreased their time at rest to maintain their grazing time [17].…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of 4-pyridoxic acid reflect vitamin B6 dysfunction [43]. The active form of vitamin B6 is involved in various enzyme reactions that are related to amino acid and lipid metabolism [34]. In contrast, defects in vitamin B6 affected antioxidant defenses in animal livers [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of constituents of a sample by hyphenated techniques such as gas chromatography -mass spectrometry (GC/MS) is called profiling. With the help of these techniques, a comprehensive chromatographic profile of a sample with the relative or absolute quantification of all compounds of the sample could be obtained 4 . It is estimated that in plant kingdom approximately 200,000 compounds may be present and of these, about 10,000 are known 5 .…”
mentioning
confidence: 99%
“…Such methods have high accuracy and precision which is further increased with the use of stable isotope labelled internal standards. But, stable isotope labelled standards are highly expensive and are commercially available only for a limited number of compounds 4 . In non-targeted analysis all compounds which show peaks above certain intensity, can be characterized on the basis of their GC retention indices and mass spectral patterns.…”
mentioning
confidence: 99%